Estudo comparativo do conforto e efeitos adversos de interfaces para ventilação não invasiva em voluntários sadios - Reis, Ricardo (2006)
Rationale: Non-invasive ventilation (NIV) is defined as a ventilatory support technique using an interface (usually a mask) instead of tracheal intubation to adapt the patient’s respiratory system to the ventilator. Although it is as efficacious as the invasive method in terms of improving gas exchange in patients with respiratory failure due to various etiologies, it remains associated with considerable failure rates. Despite the association between interface and low tolerance to NIV, few studies have been published evaluating the efficacy and safety of each type of interface. interfaces are best studied on healthy subjects avoiding the interference of confounding factors related to respiratory failure. Objective: To evaluate and compare three types of masks used as NIV interface on healthy volunteers with regard to frequency and type of adverse events and level of comfort. Method: A randomized, crossover clinical trial was conducted to evaluate and compare nasal (N), facial (F), and total face (TF) masks adapted to healthy volunteers using a flow generator ventilator with a circuit exhalation valve. The three masks were tested on all subjects in random sequence during 10 minutes each, equally divided between two levels of expiratory and inspiratory positive airway pressure (EPAP; IPAP) in bilevel ventilation: a low-pressure (LoP) setup (IPAP: 11cmH2O; EPAP: 6cmH2O) and a moderate to high-pressure (MoHiP) setup (IPAP=15cmH2O; EPAP=10cmH2O). At the end of each 5-min period, the subjects were given a standardized written questionnaire on adverse events including questions about uncomfortable pressure and pain at contact points between mask and face, unpleasant perception of air leaks, nasal and oral mucosal dryness and claustrophobia. They also recorded sensations of comfort on a 10-cm visual analogical scale (10=absence of discomfort; 0=maximum discomfort). A 10-min interval of spontaneous, mask-free breathing was allowed between each period of NIV. The respiratory rate (RR), tidal volume (TV), pulse oxymetry (SpO2) and end-tidal CO2 volume (EtCO2), measured between mask and exhalation valve, were monitored during the entire protocol. While categorized variables were analyzed with Pearson’s Chi-square test, Fisher’s exact test and McNemar’s test, continuous variables were analyzed with ANOVA and least-squares regression. Results: The study included 24 healthy volunteers (12 women) aged 18 to 35 (mean age: 25.7 years). The following was observed with regard to adverse events while using the LoP setup: a) The incidence of one or more adverse events by subject was 91.7% for N and TF and 95.8% for F; b) The number of adverse events per subject was smaller for N than for F (3.58 vs. 5.0; p=0.002) or TF (3.58 vs. 4.71; p=0.03); c) The most frequently reported adverse event was “mask pressure” (N=54.2%; F=66.7%; FT=66.7%); d) Pain at points of mask contact was less frequently reported for TF than for F (37.5% vs. 66.7%; p=0.01), but no significant difference was observed between TF and N; e) The incidence of unpleasant air leak perception around the eyes or mouth was lower for TF than for N (41.7% vs. 75%; p=0.03) but no significant difference was observed between N and F; f) Complaints of nasal or oral dryness were much less frequent for N than for F (25% vs. 62.5%; p=0.01) or TF (25% vs. 75%; p<0.001); g) Claustrophobia was more frequently reported for TF than for N (33.3% vs. 8.3%; p=0.07). The higher airway pressure of the MoHiP setup resulted in: a) The incidence of one or more adverse events per subject remained high (95.8% for both N and TF; 100% for F); b) On the average, N continued to be associated with the lowest number of adverse events per subject, the difference between N and F being statistically significant (4.75 vs. 6.04; p=0.009); c) Mask pressure remained the most common complaint (N=62.5%; F=70.8%; FT=75%); d) No significant difference was observed concerning pain; e) Reports of unpleasant air leak perception increased more for F than for TF (83.3% vs. 54.2%; p=0.09); f) N continued to be associated with the lowest incidence of dryness (N=41.7% vs. F=66.7%; p=0.03; and N=41.7% vs. TF=79.2%, p=0.02); g) The incidence of claustrophobia remained higher for TF than for N, though not statistically so (33.3% vs. 8.3%; p=0.07); h) On the average, pressure augmentation induced a higher number of adverse events per subject in all 3 mask types. The increase was statistically significant in the case of N (3.58 vs. 4.75; p=0.003) and F (5.0 vs. 6.04; p=0.007) and tended to be so for TF (4.71 vs. 5.33; p=0.07); i) No significant difference was observed between the masks with regard to comfort, but the MoHiP setup was reportedly less comfortable than the LoP setup for all mask types: N (7.54 vs. 7.1; p=0.01), F (7.50 vs. 6.54; p<0.001) and TF (7.25 vs. 6.50; p=0.001). Physiological variations observed during the protocol could not account for the adverse events or comfort sensation reported. Interestingly, the CO2 curve remained undetected by the capnograph while using TF, probably because the exhaled CO2 was completely eliminated through orifices in the mask. Conclusions: All three mask types presented a high incidence of adverse events in healthy volunteers. The nasal (N) mask was associated with a lower mean number of adverse events per subject, especially with regard to dryness. Although the total face (TF) mask seemed to be associated with fewer reports of pain and with a lower incidence of unpleasant air leak perception, claustrophobia was also more frequently reported. The masks were equally efficacious in terms of comfort. Higher pressure levels in the bilevel mode were associated with increased reports of discomfort and adverse events in healthy volunteers.